2020
DOI: 10.1093/ofid/ofaa550
|View full text |Cite
|
Sign up to set email alerts
|

Severe Acute Respiratory Syndrome Coronavirus 2 Seroprevalence Among Adults in a Tropical City of the Caribbean Area, Colombia: Are We Much Closer to Herd Immunity Than Developed Countries?

Abstract: A serological survey was carried out in Monteria (500,000 population), a mid-size city in Colombia. An overall prevalence of 55.3% (CI95% 52.5%-57.8%) was found among a sample of 1.368 people randomly selected from the population. Test positivity was related to economic characteristics with the highest prevalence found in the most impoverished areas, representing 83.8% of the city’s population. We found a prevalence that might be associated with some important level of population immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 9 publications
3
18
0
Order By: Relevance
“…Depending on vaccine coverage and effectiveness against infectiousness with future circulating variants – which may be antigenically dissimilar to B.1.1.7 [ 8 ] – herd immunity to SARS-CoV-2 in the absence of other non-pharmaceutical interventions may not be reached until considerable natural immunity has accumulated. As some countries now have a sizeable subpopulation with protective antibodies acquired through natural infection [ 9 ], we estimated the probability of reaching the HIT for SARS-CoV-2 under varying degrees of vaccination coverage against a background of reduction in transmission from natural immunity.…”
Section: Covid-19 Vaccination Coverage Needed Considering Natural Immunitymentioning
confidence: 99%
See 1 more Smart Citation
“…Depending on vaccine coverage and effectiveness against infectiousness with future circulating variants – which may be antigenically dissimilar to B.1.1.7 [ 8 ] – herd immunity to SARS-CoV-2 in the absence of other non-pharmaceutical interventions may not be reached until considerable natural immunity has accumulated. As some countries now have a sizeable subpopulation with protective antibodies acquired through natural infection [ 9 ], we estimated the probability of reaching the HIT for SARS-CoV-2 under varying degrees of vaccination coverage against a background of reduction in transmission from natural immunity.…”
Section: Covid-19 Vaccination Coverage Needed Considering Natural Immunitymentioning
confidence: 99%
“…If the B.1.1.7 variant dominates, countries with a high proportion of adults require much higher effectiveness, ca 90%, to reach the HIT after an adult immunisation campaign, and many countries with a lower adult population proportion are again unlikely to reach the HIT through vaccination. Although there are some regional and local studies in countries such as Brazil [ 14 ], Italy [ 15 ], and Columbia [ 9 ] showing high seroprevalence at the local level, much lower seroprevalence has been estimated at the national level. For countries in which there is substantial heterogeneity in natural immunity, these estimates for herd immunity are unlikely to equate to a pragmatic protective threshold.…”
Section: Controlling Sars-cov-2 Spread In Populations With Different Age Structure and Seroprevalencementioning
confidence: 99%
“…Local studies have been realized in Monteria and Bogotá. In Montería, 1368 individuals were randomly selected from the population, and between July and August 2020, a seroprevalence of 55.3% was estimated [ 26 ]; this was one of the highest seroprevalences in Colombia and Latin America for the time. A few small occupational studies have also been conducted.…”
Section: Discussionmentioning
confidence: 99%
“…In the national seroprevalence survey done by the Colombian National Institute of health (INS), crude and adjusted seroprevalence for Bogotá during October and November 2020 among 4,597 individuals was 26.3% and 30% a, respectively (19). Higher seroprevalence has been described for cities in the Caribbean area of Colombia reaching up to 55.3% (20). In a study carried in a university hospital in Bogotá during the first peak showed a baseline seroprevalence of 2.28% among health workers, increasing to 5.98% after 2-4 weeks of follow; with 38% of individual being pre-symptomatic or asymptomatic (21).…”
Section: Discussionmentioning
confidence: 99%